Outdoors class - Gordon, John C. (photographer):::Creator::::::::::::
This image depicts a class being held outdoors at an unidentified school. Students sit on the lawn facing a blackboard. In front of the class next to the blackboard is a radio and speaker. A female teacher stands at the back of the class. Behind her, a man appears to be filming the scene. The blackboard reads: "Hoover, our new President. 1. Nation's debt to Coolidge. 2. Enforcement of law necessary to our country's welfare. 3. America's leadership to the nations of the world."